Exosome mediated transfer of miRNA‐140 promotes enhanced chondrogenic differentiation of bone marrow stem cells for enhanced cartilage repair and regeneration. Issue 7 (24th February 2020) - Won Lee, Gi; Thangavelu, Muthukumar; Joung Choi, Min; Yeong Shin, Eun; Sol Kim, Han; Seon Baek, Jong; Woon Jeong, Young; Eun Song, Jeong; Carlomagno, Cristiano; Miguel Oliveira, Joaquim; Luis Reis, Rui; Khang, Gilson
Abstract: Exosomes (EXs) are nanocarrier vesicles with 20‐50 nm dimensions. They are involved in cell proliferation and differentiation and in protecting the integrity of materials. They can be isolated from plasma and immunoreactive components. Recent studies demonstrated their potential role in cartilage regeneration. To enhance their regenerative effect, molecules like microRNA (miR‐140) can be loaded in EX that acts as RNA delivery systems. In this study, we combined EX with miR‐140 to enhance cell differentiation by inducing membrane fusion and consequent miRNA released into the cytoplasm. The carrier RNA complex was successfully synthesized through freeze and thaw method leading to the formation of EX‐containing miR‐140. The EX morphology was assessed through transmission electron microscopy and their miR‐140 uptake efficiency through real‐time polymerase chain reaction (RT‐PCR). The effects on bone marrow stem cells (BMSCs) were evaluated by in vitro cell culture. Cell adhesion and morphology were studied using a bio‐scanning electron microscope and confocal laser scanning microscope. Differentiation BMSCs into chondrocytes was analyzed by RT‐PCR and histology. Our results confirm the bioactive role of EX loaded with miR‐140 in the differentiation of BMSCs into chondrocytes. EXs were biocompatible involving in the cartilage healing process through chromogenic differentiation of BMCS exploiting the tissue engineering route. Abstract : Improving the efficiency of gene delivery carrier loading microRNA in exosome.